Validation of the Instrument ‘Metacognitive Awareness Inventory (Mai)’ With Students in Colombia - Huertas Bustos, Adriana Patricia; Vesga Bravo, Grace Judith; Galindo León, Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The object of this study was to adapt and prove the survey referred as ‘Metacognitive Awareness Inventory’ in order to try it out with population in Colombia. This instrument, known as MAI, and created by Schraw &amp, Denninson in 1994 to identify the metacognitive awareness in subjects, has 52 items distributed in eight categories: declarative knowledge, procedural knowledge, conditional knowledge, planning, organization, monitoring, refinement, and assessment. This survey was applied to 536 students in tenth and eleventh grades at public and private schools in Bogota, through a computer application designed for this study. Information was gathered via web and data were analyzed with the help of the SPSS. The Cronbach’s alpha of the survey ranged 0.94, and from 0.61 to 0.71 for the eight categories. The results allow to conclude that the MAI developed in Colombia is a valid and reliable instrument, which can be useful for further researches aimed at knowing about students’ metacognitive awareness.